Implementasi Kebijakan Pengelolaan Parkir Kota Bandung - Asep Hidayat; Aris Munandar; Armidiana Armidiana (Department of Public Administration, 2018)
The Parking Tax Revenue, from 2013 to 2016, experienced ups and downs and less significant increase, especially in 2015, it run into a very significant decrease from the target. This study aims to analyze the implementation of parking management policy in buildings and parking lots in Bandung. The Research uses a qualitative approach, with descriptive research type. Data collection techniques used are in-depth interviews and literature study. The determination of informants in this study was carried out using the purposive technique. To analyze the data, this research uses qualitative data analysis, namely by searching and systematically compiling data obtained from interviews, field notes, and other materials. The results of this study indicate that the implementation of Peraturan Wali Kota No. 1005 of 2014 regarding Parking Lease Prices and Technical Guidelines for Parking Management in Buildings and Parking Grounds in Bandung City has not been running optimally, because it has been seen from several factors that influence it.